Nanostructural arrangements and surface morphology on ureasil-polyether films loaded with dexamethasone acetate - Oshiro, Joao Augusto; Lusuardi, Angelo; Beamud, Elena M.; Chiavacci, Leila Aparecida [UNESP]; Cuberes, M. Teresa (MDPI, 2021)
Ureasil-Poly(ethylene oxide) (ureasil-PEO500) and ureasil-Poly(propylene oxide) (u-PPO400) films, unloaded and loaded with dexamethasone acetate (DMA), have been investigated by car-rying out atomic force microscopy (AFM), ultrasonic force microscopy (UFM), contact-angle, and drug release experiments. In addition, X-ray diffraction, small angle X-ray scattering, and infrared spectroscopy have provided essential information to understand the films’ structural organization. Our results reveal that while in u-PEO500 DMA occupies sites near the ether oxygen and remains absent from the film surface, in u-PPO400 new crystalline phases are formed when DMA is loaded, which show up as ~30–100 nm in diameter rounded clusters aligned along a well-defined direc-tion, presumably related to the one defined by the characteristic polymer ropes distinguished on the surface of the unloaded u-POP film; occasionally, larger needle-shaped DMA crystals are also observed. UFM reveals that in the unloaded u-PPO matrix the polymer ropes are made up of strands, which in turn consist of aligned ~180 nm in diameter stiffer rounded clusters possibly formed by siloxane-node aggregates; the new crystalline phases may grow in-between the strands when the drug is loaded. The results illustrate the potential of AFM-based procedures, in combination with additional physico-chemical techniques, to picture the nanostructural arrangements in polymer matrices intended for drug delivery.
Keywords: Atomic force microscopy; Organic-inorganic hybrid films; Sol-gel; Ultrasonic force microscopy